The microstructure and mechanical properties of Mg-Gd-Y-Zn-Zr system and Mg-Gd-Y-Zr system alloys by RUE deformation - Leichen Jia; Jianmin Yu; Wenlong Xu; Guoqin Wu; Qing Xia; Zhimin Zhang (Materials Research Express, 2021)
This study investigates the effects of long-period stacking order (LPSO) phases on the dynamic recrystallization (DRX) process. By comparing Mg-Gd-Y-Zn-Zr (GWZ) alloy and Mg-Gd-Y-Zr (GW) alloy deformed by 4 passes of Isothermal Reciprocating Upsetting-Extrusion (RUE), the initial alloy grain sizes are 113.4 μ m and 88.2 μ m, respectively, after 4 passes, the grain size becomes 3.5 μ m and 4.8 μ m, and the grain refinement of GWZ is greater. After 1 pass, the DRX volume fraction of GWZ alloy is 83% and 15%, which is related to the LPSO phases contained in the GWZ alloy. The texture strength of the GWZ alloy ranges from 8.5 of 1 pass to 2.2 of 4 passes, while the GW alloy is from 5.9 of 1 pass to 2.8 of 4 passes, mainly due to the DRX grain volume fraction. The tensile test results at room temperature (RT) showed that the ultimate tensile strength (UTS) and tensile yield strength (TYS) of GWZ alloy are higher than that of GW alloy, and the elongation is lower than that of GW alloy.